Papaver in polish oral literature - Orzechowska, Sara (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Papaver is popular component in European mythologies, fairy tales, rituals and short forms of folklore (oral literature), it appears as a specific cultural construct. Main goal of the article is to analyze the meanings of this plant occured in Polish folk tales, referring also to cultural practice and phytotherapeutic knowledge, which is the source of symbolism connecting papaver with the dream world, death, demonic creatures and initiation in traditional folklore. The lifespan of the papaver in the ethnobotanical consciousness of Poles definitely distinguish oneself from other herbs, it is proved by surveys conducted for the purposes of the article. Changes in economic and cultural realities have resulted in a sharp decline of herbal knowledge, the disappearance of rituals and magical practices (including this with use of poppy seeds) in Poland, nevertheless papaver is still a plant which physiological effect and an important place during holidays (most often Christmas) is known to almost everyone in Poland. Contemporary oral literature with the papaver component refers mainly to the home-made production of drugs with opium, it creates new plot content (also with comic elements), which passages are included in the article. These strands enrich the resources of Polish folklore about plants.